Novel mRNA-silencing bodies at the synapse: A never-ending story - Thomas, Maria Gabriela (2016)
Several cellular responses depend on translational regulation and in most cases, this involves the formation of cytoplasmic granules that contain repressed mRNAs. In neurons, numerous mRNAs travel along dendrites to be locally regulated upon synapse activity and we have recently shown that the exoribonuclease XRN1 forms dynamic aggregates at the post synapse that respond to specific stimuli.(1) These foci were termed SX-bodies and are distinct from stress granules (SGs), processing bodies (PBs) and other RNA granules previously described. Together with Smaug1-foci and FMRP-granules, the SX-bodies contribute to dynamically shape the transcriptome available for translation at the post-synapse.